Experimental sexual selection affects the evolution of physiological and life history traits - Garlovsky, Martin D.; Holman, Luke; Brooks, Andrew L.; Snook, Rhonda R.; Novicic, Zorana K. (Dryad, 2021)
Sexual selection and sexual conflict are expected to affect all aspects of
the phenotype, not only traits that are directly involved in reproduction.
Here, we show coordinated evolution of multiple physiological and life
history traits in response to long-term experimental manipulation of the
mating system in populations of Drosophila pseudoobscura. Development time
was extended under polyandry relative to monogamy in both sexes,
potentially due to higher investment in traits linked to sexual selection
and sexual conflict. Individuals (especially males) evolving under
polyandry had higher metabolic rates and locomotor activity than those
evolving under monogamy. Polyandry individuals also invested more in
metabolites associated with increased endurance capacity and efficient
energy metabolism and regulation, namely lipid and glycogen. Finally,
polyandry males were less desiccation- and starvation- resistant than
monogamy males, suggesting trade-offs between resistance and sexually
selected traits. Our results provide experimental evidence that mating
systems can impose selection that influences the evolution of non-sexual
phenotypes such as development, activity, metabolism, and nutrient
homeostasis.
Data is provided as a single zipped folder containing five .csv files and
a README.txt file. Detailed description of methods can be found in the
supplementary material accompanying the manuscript. All analyses can be
found at https://lukeholman.github.io/exp_evol_respiration/
Please see the README.txt provided in the zipped folder.
Keywords: polyandry; starvation resistance; Development time; Drosophila pseudoobscura